Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1991
DOI: 10.1007/bf03346869
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones in tissues from human embryos and fetuses

Abstract: This study was intended to quantify T3 and T4 in various human tissues at different stages of gestation as a contribute in the evaluation of the role of thyroid hormones in fetal development, particularly before the maturation of fetal thyroid function. Moreover, for a better comprehension of the influence of thyroid hormone status in tissues, the study was extended to adults. Embryonic specimens were obtained from voluntary abortions between 6 and 12 weeks of gestation, fetal and neonatal specimens from fetus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 33 publications
0
25
0
Order By: Relevance
“…Current evidence points to a direct role for maternal TH in human fetal CNS development from the 1 st trimester of pregnancy [4,5] and this necessitates the transplacental passage of 60 maternal TH to the fetus. Transplacental transport of maternal TH is evidenced by the finding of a biologically significant concentration of free thyroxine (T4) in fetal coelomic fluid and in fetal tissues from as early as five weeks of gestation [6,7]. Even at term, the concentration of maternally-derived T4 in the circulation of fetuses with absent endogenous thyroid function reaches 25-50% of normal [8].…”
Section: Introductionmentioning
confidence: 99%
“…Current evidence points to a direct role for maternal TH in human fetal CNS development from the 1 st trimester of pregnancy [4,5] and this necessitates the transplacental passage of 60 maternal TH to the fetus. Transplacental transport of maternal TH is evidenced by the finding of a biologically significant concentration of free thyroxine (T4) in fetal coelomic fluid and in fetal tissues from as early as five weeks of gestation [6,7]. Even at term, the concentration of maternally-derived T4 in the circulation of fetuses with absent endogenous thyroid function reaches 25-50% of normal [8].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, patients with AD have been shown to have significantly increased rT3 levels and an increased rT3 to T4 ratio in the CSF [33]. Taken together, these findings suggest abnormal intracerebral metabolism of THs and possibly brain hypothyroidism in AD [34]. Although the A high concentration of glucocorticoid receptors exists in the hippocampus, and this brain region is thought to be involved in the negative-feedback mechanism of glucocorticoid secretion [35].…”
Section: Discussionmentioning
confidence: 93%
“…It has been suggested that local tissue conversion to biologically active T 3 may occur in fetal tissues. T 3 nuclear receptors, binding of T 3 , and increasing binding capacity are all present in human fetal lung tissue at 12-19 wk of gestation and in other species at comparable times (6,13,18,23). Thus low levels of endogenous T 3 may play a role in lung morphogenesis during the early pseudoglandular period of lung development.…”
Section: Discussionmentioning
confidence: 93%
“…T3 levels in human embryonic lung are 0.5 nM, and the nuclear binding coefficients of T3 receptors in rodent embryonic lung have been shown to be 0.5 nM. A similar range of T 3 concentrations has also been used in cultured fetal lung and showed a dose-response effect on surfactant phospholipid synthesis (13,25,26,36). Cultured lungs were maintained at 37°C in 95% room air-5% CO2 for the 72 h of culture.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation